2015
DOI: 10.1016/j.isprsjprs.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimating deformation due to soil liquefaction in Urayasu city, Japan using permanent scatterers

Abstract: In Japan, several cities endured severe damage due to soil liquefaction phenomenon, which was developed in association with the massive shaking of the 2011 Tohoku earthquake. Measuring soil liquefaction deformations was not an easy task, mainly because of the total loss of signal coherence in the affected regions. In this paper, we present our approach to estimate the deformations associated with soil liquefaction using interferometric synthetic aperture radar techniques. We use a stack of coseismic interferog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…These local surface displacements were associated with likely groundwater level changes at several locations on the plain. It has been reported that soil liquefaction occurred extensively in artificial filled areas along the Tokyo bay, which are ~20-50 km away from the local uplift area in this study (Bhattacharya et al 2011;Ishitsuka et al 2012;ElGharbawi and Tamura 2015b). Soil liquefaction is the compaction of soil grains from continuous vibration.…”
Section: Possible Mechanisms Of Local Surface Upliftmentioning
confidence: 70%
“…These local surface displacements were associated with likely groundwater level changes at several locations on the plain. It has been reported that soil liquefaction occurred extensively in artificial filled areas along the Tokyo bay, which are ~20-50 km away from the local uplift area in this study (Bhattacharya et al 2011;Ishitsuka et al 2012;ElGharbawi and Tamura 2015b). Soil liquefaction is the compaction of soil grains from continuous vibration.…”
Section: Possible Mechanisms Of Local Surface Upliftmentioning
confidence: 70%
“…ElGharbawi and Tamura [35] reported that a tilted building could be a signature of a local deformation. Assuming that all buildings in the northern urban area of Guanmiao district tilted only 0.5 • toward the west direction, this would make a house 10 m in height (approximately three floors) move 87 mm in a westerly direction.…”
Section: Surface Deformation In Guanmiao Districtmentioning
confidence: 99%
“…The analysis of coherence variation has been successfully applied in many fields of Earth sciences, including volcanology, landslide hazard and earthquake hazard [28][29][30]. Among the earthquake hazards, the decorrelation characteristic is useful for detecting the surface deformation and cracks [30,31], distinguishing the collapsed and damaged buildings [31,32] and mapping the ranges of soil liquefaction [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the challenges of field observation immediately after the event, remote sensing has become an effective technique for reliable disaster assessment and post-earthquake emergency response [3][4][5]. With the rapid development of the technology, remote sensing has played an increasingly important role in disaster assessment, rescue and relief, as well as recovery and reconstruction, due to its advantages, such as improved safety, rapid and comprehensive data collection, macroscopic and large coverage and freedom from the restrictions of ground natural conditions [6][7][8]. It is extremely important to obtain highquality data sources in time for earthquake damage monitoring and emergency rescue by means of remote sensing [9,10].…”
Section: Introductionmentioning
confidence: 99%